Crisis Changes Lithuania: Alterations of the Society and the State in 1931–1935 - Butkus, Zenonas; Černiauskas, Norbertas (Lietuvos istorijos studijos, 2016)
The article examines changes of the socio-economic situation in Lithuania in the 1940s during the crisis (1931–1935). These changes influenced a wider alteration of the Lithuanian society. The article reveals the specifics of the crisis in Lithuania, the economic instruments of the government and propagandistic programs, which affected the attitude of farmers to the agricultural traditions. Organized Lithuanian business structures promptly appeared during the crisis, as well as the society became more economically active and creative.